Factors Causing Injuries in the Game of Football: Literature Review - Azmi, Mohammed Faiznur; Julianur, Julianur (Journal of Educational Sciences, 2025)
This article discusses the factors that cause injuries to soccer players through a literature review based on secondary data from various indexed journals. In general, the causes of injuries can be divided into external and internal factors. External factors include sports equipment (shoes, balls) and non-ideal field conditions, such as uneven, slippery, or muddy surfaces. Meanwhile, internal factors include body anatomy (such as leg length imbalance or foot deformity), technical errors (such as incorrect shooting techniques), decreased muscle strength, low fitness, and overuse injuries. Injuries most often occur in the ankle, either due to physical contact or non-contact. Physical condition factors such as power, speed, flexibility, and agility, as well as mastery of shooting techniques, have a significant correlation with the risk of injury. With this understanding, it is hoped that athletes can minimize injuries through more thorough preparation.